Marco Aurelio Emperador y Justino Mártir - Sánchez, Javier Antolín (Estudio agustiniano, 2019)
Justin Martyr and Marcus Aurelius are two figures of Greco-Roman culture, live and develop their philosophical activity during the second century and understand philosophy as a way of life. Christianity at this time was understood also as a way of life, that is, it participated in the same philosophical conception of the schools of antiquity since it proposed a way of life. Saint Justin is martyred in the year 165 during the reign of Marco Aurelius, a philosopher who distinguished himself by a message of peace and universal brotherhood. In our study we seek a dialogue between